Dimensionamento da carga térmica de uma academia - Santos, Ruanna de Paiva (Universidade Federal Rural do Semi-Árido, 2019)
For an environment to be within the parameters of thermal comfort it is necessary to know the amount of sensible and latent heat that must be added or removed from the place, called thermal load. Several factors affect the calculation of thermal load such as lighting, occupants, conducting heat to the walls and windows. With the objective of dimensioning the thermal load of a gym and selecting a device with adequate capacity, the necessary calculations were made. It was noticed that the thermal load due to the occupants and due to the conduction and insolation of the roof presented higher values when compared to the other factors analyzed. At the end it was concluded that for an area of 259.53 m², eight air-conditioning units with a capacity of 48,000 BTUs each one.
Monografia
Keywords: Conforto térmico; Ar-condicionado; Carga térmica; ENGENHARIAS::ENGENHARIA MECANICA